2020
DOI: 10.1038/s41390-020-0852-3
|View full text |Cite
|
Sign up to set email alerts
|

The human milk oligosaccharides 2’-fucosyllactose and 6’-sialyllactose protect against the development of necrotizing enterocolitis by inhibiting toll-like receptor 4 signaling

Abstract: Objective: Necrotizing enterocolitis (NEC) develops through exaggerated toll-like receptor 4 (TLR4) signaling in the intestinal epithelium. Breast milk is rich in non-digestible oligosaccharides and prevents NEC through unclear mechanisms. We now hypothesize that the human milk oligosaccharides 2’-Fucosyllactose (2’-FL) and 6’-Sialyllactose (6’-SL), can reduce NEC through inhibition of TLR4 signaling. Design: NEC was induced in newborn mice and premature piglets and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 30 publications
1
114
1
2
Order By: Relevance
“…Notably, the risk of gastro-intestinal infections was shown to be lower in breast-fed infants from FUT2 positive women [ 27 ], whereas the risk of allergic disease was reduced with increasing levels of 2′FL in milk [ 28 ]. We speculate that our results may, at least partially, explain these observations, as well as the protective effect of 2′FL against intestinal inflammation shown in experimental models of necrotizing enterocolitis [ 29 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Notably, the risk of gastro-intestinal infections was shown to be lower in breast-fed infants from FUT2 positive women [ 27 ], whereas the risk of allergic disease was reduced with increasing levels of 2′FL in milk [ 28 ]. We speculate that our results may, at least partially, explain these observations, as well as the protective effect of 2′FL against intestinal inflammation shown in experimental models of necrotizing enterocolitis [ 29 ].…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, direct anti-inflammatory effects of HMOs previously shown in Caco 2 cultures [ 31 ] may have dampened the impact of the cytokine challenge on the barrier integrity. HMOs, in particular 2′FL, were shown to prevent inflammation trough inhibiting TLR4 signaling [ 29 ] and CD14 expression [ 32 ]. Other mechanistic studies are required to better understand the specific modulation of the barrier by 2′FL and the unspecific protection brought by the combinations of the other HMOs.…”
Section: Discussionmentioning
confidence: 99%
“…HMOs also reduce the risk of infections, by acting as antimicrobials that can mimic structures of viral receptors, providing a competitive advantage in preventing viral attachment to intestinal cells [ 3 ]. Finally, HMOs have proven beneficial toward the protection from necrotizing enterocolitis [ 4 ] and can signal to intestinal epithelial cells influencing gene expression, gastrointestinal development, and dampening inflammation [ 5 ]. Environmental and/or maternal factors that influence biosynthesis and composition of HMOs could, in theory, have a profound impact on these beneficial aspects of HMOs for breastfed infants.…”
Section: Introductionmentioning
confidence: 99%
“…Infant fecal HMO concentrations change over time and correlate with a shift in the fecal microbiota from a non-saccharolytic population dominated by commensals of the birth canal to a population dominated by saccharolytic microbes (46) Several randomized controlled trials showed that infants fed with a formula supplemented with the HMOs 2 ′ -FL ± lacto-N-neotetraose or galacto-oligosaccharides develop a distinctive stool bacterial population compared to infants fed a control formula which is more similar to that of breastfed infants (increased colonization with Bifidobacteria and Lactobacillus and decreased colonization with pathobionts) and was accompanied by a lower plasma inflammatory cytokine concentrations (47)(48)(49)(50). In vitro, HMOs prevented the intestinal epithelial attachment of enteropathogenic Escherichia (E.) coli but whether this was a direct or indirect effect remained elusive (114) With respect to the mode of action, HMOs were shown to modulate also toll-like receptor (TLR)-dependent proinflammatory signaling, while elevating cytokines involved in tissue repair and homeostasis (115)(116)(117). However, these effects could not be linked to the gut microbiota-shaping effect so far.…”
Section: Human Milk Oligosaccharides (Hmos)mentioning
confidence: 99%